1997
DOI: 10.1093/ndt/12.10.2105
|View full text |Cite
|
Sign up to set email alerts
|

Poor pre-dialysis glycaemic control is a predictor of mortality in type II diabetic patients on maintenance haemodialysis

Abstract: We conclude that poor glycaemic control before starting dialysis is a strong predictor of cardiovascular morbidity and survival for type II diabetics on haemodialysis. These results imply that better glycaemic control before dialysis might be important in improving the long-term prognosis in type II diabetics on haemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
6
8

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(103 citation statements)
references
References 3 publications
2
87
6
8
Order By: Relevance
“…However, a recent cohort study of type 2 diabetes indicated diminished cardiovascular benefit from intensive blood glucose control in patients with high levels of comorbidity (24). Until the past few years, there had been few studies that examined the association between HgbA1c and clinical outcomes in the diabetic dialysis population (25)(26)(27), most of them small observational studies performed outside of the United States. Limited data from older studies appeared to suggest that poor glycemic control in patients with diabetes on dialysis was associated with increased morbidity (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent cohort study of type 2 diabetes indicated diminished cardiovascular benefit from intensive blood glucose control in patients with high levels of comorbidity (24). Until the past few years, there had been few studies that examined the association between HgbA1c and clinical outcomes in the diabetic dialysis population (25)(26)(27), most of them small observational studies performed outside of the United States. Limited data from older studies appeared to suggest that poor glycemic control in patients with diabetes on dialysis was associated with increased morbidity (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have shown beneficial impact of predialysis glycemic control on survival after initiation of dialysis (6,7). In addition, limited studies showed an association of poor glycemic control with poor survival on chronic dialysis (8,9).…”
Section: In Diabetic Patients Glycemic Control Has An Essential Rolementioning
confidence: 99%
“…Although these trials excluded patients on hemodialysis, it has been argued that better glycemic control is key toward preventing DM‐related complications in this population 3, 7, 8, 9. In fact, surprisingly few studies have investigated the association between HbA 1c and clinical outcomes in the dialysis population 3, 10, 11, 12, 13, 14, 15, 16. Most of these studies focused only on all‐cause mortality as the outcome and were limited by small sample size and correspondingly low statistical power 11, 12, 13, 15…”
Section: Introductionmentioning
confidence: 99%